STUDI PENGEMBANGAN DAN PEMASARAN KASOAMI DI KELURAHAN WANCI KECAMATAN WANGI-WANGI KABUPATEN WAKATOBI - Wardana Wardana; Muzuna Muzuna (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2020)
Kasoami is a traditional food in Wakatobi Regency which has to contend with modern food like rice. This study aims to determine the efforts made by Kasoami craftsmen in maintaining their business in the midst of competition with other food products and to figure out the development and marketing strategies of Kasoami. The collected data were analyzed descriptively and SWOT. The conclusions are: the efforts made by craftsmen in maintaining their business are learning to improve product quality, shelf life, and good packaging of Kasoami which are equipped with production labels according to applicable standards. The product development strategies based on strengths and opportunities owned by craftsmen are: Promoting Kasoami as a quality and healthy product through online media; Collaborating with distributors and tourism agents; Providing excellent service to customers; Increasing the amount of production; Strategies based on utilizing opportunities to face weaknesses are craftsmen: Need to learn a good business management system; Need to learn to create a kasoami that has a unique and delicious taste; It is necessary to utilize a distributor agent; Need to get infrastructure assistance to increase production capacity from the government or private parties; Strategy for developing products based on strength to face threats are: Increase competitiveness and maintain quality; Reducing dependency on fuel oil; Increase product creativity and use of materials as efficiently as possible. Keywords: Development studies, kasoami, marketing, SWOT